2019
DOI: 10.1111/infa.12307
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal risk and physical aggression during the first years of life: The gender‐specific role of inhibitory control

Abstract: Prenatal risk and a lack of inhibitory control have consistently been related to the development of physical aggression in older children. This study examined whether inhibitory control mediated the relation between prenatal risk and aggression in infants and toddlers. The role of gender in this mediation model was also examined. The sample consisted of 161 mother–child dyads (83 boys). A prenatal cumulative risk score was created from a number of well‐established risk factors including maternal psychopatholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 90 publications
(174 reference statements)
1
9
0
Order By: Relevance
“…Converging support for Moffitt’s (1993) proposal that EF sets the stage for early externalizing behavior comes from three previous longitudinal studies that have adopted cross‐lagged designs in preschool and school‐aged children (Hughes & Ensor, 2008; Sulik et al., 2015; Kahle et al, 2018). While prior studies point to a link between related constructs like effortful control and externalizing behavior in the second year of life (e.g., Adrichem et al., 2019; et al., 2000), to date cross‐lagged analyses in this age range have not been undertaken. The current study extends the developmental scope of research on the executive account of externalizing behavior by examining the nature and direction of this association in children under the age of two.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Converging support for Moffitt’s (1993) proposal that EF sets the stage for early externalizing behavior comes from three previous longitudinal studies that have adopted cross‐lagged designs in preschool and school‐aged children (Hughes & Ensor, 2008; Sulik et al., 2015; Kahle et al, 2018). While prior studies point to a link between related constructs like effortful control and externalizing behavior in the second year of life (e.g., Adrichem et al., 2019; et al., 2000), to date cross‐lagged analyses in this age range have not been undertaken. The current study extends the developmental scope of research on the executive account of externalizing behavior by examining the nature and direction of this association in children under the age of two.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, effortful control at 22 months was negatively correlated with externalizing behaviors at age 6 (Kochanska & Knaack, 2003). More recently, Adrichem, Huijbregts, Van der Heijden, van Goozen, and Swaab (2019) reported negative associations between infant effortful control at 12 months (observed during a parent-child dyadic interaction)…”
Section: Executive Function and Externalizing Behaviormentioning
confidence: 96%
See 1 more Smart Citation
“…It has been shown that a cumulative risk model is more parsimonious, more ecologically relevant, and statistically more powerful in predicting behavioral development compared to specific patterns of individual risk factors (Evans et al, 2013;Flouri & Kallis, 2007;Sameroff et al, 2004). Studies using the cumulative risk approach have shown that a higher number of risk factors are clearly related to higher levels of aggressive behavior during early childhood (Bennett et al, 2013;Gassman-Pines & Yoshikawa, 2006;Trentacosta et al, 2008;Wallander et al, 2019).…”
Section: Risk In Relation To Aggressive Behaviormentioning
confidence: 99%
“…With respect to age and sex, given that preschoolers' abilities increase with age (Garon et al, 2008;Huang & Su, 2012;Wellman & Liu, 2004 ), we expected that preschoolers' polite lie-telling would increase with age (Hypothesis 4). Finally, given previous findings (Kuhnert et al, 2017;Li et al, 2018;van Adrichem et al, 2019;Walker, 2005 ), we expected these abilities to be more closely related to polite lietelling in girls than in boys (Hypothesis 5).…”
Section: The Current Studymentioning
confidence: 91%